VD_FINDINFO HC / 2013 / 273 vom 18. März 2013 - VD Tribunal cantonal (2013)
APPEL EN CAUSE, CONNEXITÉ MATÉRIELLE, ACTION RÉCURSOIRE | 319 let. b ch. 1 CPC (CH), 320 CPC (CH), 81 al. 1 CPC (CH), 82 al. 4 CPC (CH)